Evaluation of the Cases who Applied to University Hospital Child and Adolescent Mental Health Committee Because of Sexual Abuse - Birsen Şentürk Pilan; Serpil Erermiş; Tuğçe Özcan; Reyhan Çalışan; Ilayda Barankoglu; Ahsen Kaya; Ender Şenol; Hülya Güler; Ahmet Acarer; Tezan Bildik (Galenos Publishing House, 2021)
Objective: The aim of this study was to examine the sociodemographic characteristics, psychiatric diagnoses and factors associated with psychiatric diagnoses of children and adolescents who are victims of sexual abuse. Method: The files of 92 children and adolescents aged between 0-18 who were referred to University Hospital Child and Adolescent Psychiatry Forensic Policlinic between January 2017 and December 2019 due to sexual abuse were evaluated retrospectively. Psychiatric diagnoses of the cases were made according to DSM 5 diagnostic criteria. Intellectual capacity of the cases was evaluated according to the latest verison of Wechsler Intelligence Scale for Children. Results: In our study, 78 (84.8%) cases were female and 14 (15.2%) were male. Mean age of the cases was 14.1+-3.88 years. The most common type of sexual abuse was touching (52.2%, n=48). There was a psychiatric diagnose in 50 (54.3%) of them. The most common psychiatric diagnoses were posttraumatic stress disorder (n=29, 31.5%) and major depressive disorder (n=25, 27.2%). The rate of psychiatric diagnosis was significantly higher in cases exposed to coercion and violence (p=0.032). In 32 cases (34.8%), it was determined that the abuser was within the family. Conclusion: Sexual abuse has an effect on child's development throughout life.In our study, the rate of psychiatric diagnosis was high. It is very important to provide the necessary psychiatric support to the victims of sexual abuse. With the studies to be done in this area, awareness can be increased and necessary precautions can be taken.